The Effectiveness of HRV-Biofeedback Technology and Heart Rate Variability on Intercultural Communication Competence among Postgraduate Students from Different Nationalities - Sarwari, Abdul Qahar; Muhammad Nubli, Abdul Wahab (Globeedu Group, 2017)
Communication competence is an essential factor for all individuals, especially for those profession also who are deeply bounded into the collaborative settings of work and professions. Thus, it is important to assess the potential factors that could influence communication competence of individuals from various backgrounds. However, the available works on communication were mostly conducted based on the self-reported answers of individuals. Thus, this study has applied the heart rate variability (HRV)-biofeedback technology to extend the findings. This study was conducted by the participation of 60 postgraduate students of a public university, and the participants were from 17 different countries. This study was carried out through the application of a mixed methods research design, which included the quantitative and the HRV data sets. Based on the results, there were some significant correlations between the levels of HRV and the main attributes of intercultural communication competence of the participants. The results also confirmed the effectiveness of the use of HRV training and HRV-biofeedback technology on the increase of communication competence among individuals from various backgrounds. Based on the results, individuals with good levels of HRV possess good intercultural communication competence as well. The results from this study may open a new window on the relationship between HRV-biofeedback and intercultural communication competence in the field of communication.